2018
DOI: 10.1186/s13019-018-0758-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated right superior vena cava draining into the left atrium in a child with vein of Galen aneurysmal malformation—case report

Abstract: BackgroundIsolated right Superior Vena Cava drainage into the left atrium in the absence of other cardiac anomalies is an extremely rare condition. The vein of Galen aneurysmal malformation is a congenital vascular malformation. It comprises 1% of all pediatric congenital anomalies. The association vein of Galen aneurysmal malformation, with congenital heart disease has been described.Case presentationWe describe a 16-months old toddler presenting at 7-months of age with respiratory distress and cyanosis. CT b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Worldwide incidence is less than 0.5% of all CHD [ 3 ]. Similar cases were reported in KSA [ 4 , 5 ]; however, the actual national incidence is not known.…”
Section: Discussionsupporting
confidence: 66%
“…Worldwide incidence is less than 0.5% of all CHD [ 3 ]. Similar cases were reported in KSA [ 4 , 5 ]; however, the actual national incidence is not known.…”
Section: Discussionsupporting
confidence: 66%
“…There are several cases of this defect in association with other congenital heart defects and heterotaxy, but through our review only 42 cases of this as an isolated anomaly have been reported in the English literature to date 1,3‐43 . Table 1 summarizes the reported cases as case number, year of publication, first author, age and gender of patient, presentation, method of diagnosis, and the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…VoGMs are exceptionally rare with an incidence of only 1 in 3 million. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Therefore, we elected to supplement our case series with additional cases from the literature to further characterize VoGMs subtypes I-IV in greater detail. This constitutes the second major limitation, namely selection bias, because authors generally tend to report their better cases only.…”
Section: Limitationsmentioning
confidence: 99%